Students' perception on teaching and learning mathematics in english - Nordin, Aziz (Fakulti Pendidikan, UTM, 2005)
Students use language to communicate and to understand mathematics concepts. Language influences students’ thought by molding perception and structuring ideas. However, in recent years, science and mathematics in lower secondary subjects have been taught in English.This may create problems in learning these subjects.Therefore, this research was carried out to gather information and to get the clearer picture on what have happened regarding the teaching and learning science and mathematics in schools. The research instrument was a set of 16-item questionnaire that was designed to identify students’ perception on teaching and learning mathematics. The respondents consist of 279 lower secondary school students from three schools in rural area of Johor, Malaysia. The research found out that the respondents agreed to the importance of English Language in everyday life as well as career opportunity however they felt that learning science and mathematics was very difficult and demanding.This is due to the lack of ability in understanding of the subject matters and the instruction language. The result also showed that learning science is more difficult than learning mathematics. Finally, the findings revealed that there are challenges for the science and mathematics teachers to work wisely in order to overcome students’ learning difficulties and to promote effective learning among students.